1985
DOI: 10.1016/0014-5793(85)80344-6
|View full text |Cite
|
Sign up to set email alerts
|

‘Red pigment’ from ADE‐2 mutants of S. cerevisiae prevents DNA cleavage by restriction endonucleases

Abstract: Protection of DNA from cleavage by restriction endonucleases EcoRI, HindIII, BumHI, and BgfII with red pigment, produced by ADE-2 mutants of Sacchuromyces cerevisiue is demonstrated. Purification of yeast DNA from pigment can be achieved by chromatography on hydroxyapatite columns. ADE-2 locusRed pigment Restriction endonuclease (S. cerevisiae)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Of the purines, adenine is particularly critical for cell viability, maintenance, and adaptation to environmental changes due to its direct structural role in the nucleotide moieties of DNA, RNA, and high‐energy intermediates and to its participation in stress‐induced regulatory pathways. Mutations in the purine biosynthetic pathway in yeast at the ADE1 and ADE2 loci have been studied (Crowley and Kaback, 1984; Meskauskas et al, 1985; Myasnikov et al, 1991). These mutations are used to examine purine metabolism and turnover in yeast and are general nutritional markers for recombinant strains.…”
Section: Introductionmentioning
confidence: 99%
“…Of the purines, adenine is particularly critical for cell viability, maintenance, and adaptation to environmental changes due to its direct structural role in the nucleotide moieties of DNA, RNA, and high‐energy intermediates and to its participation in stress‐induced regulatory pathways. Mutations in the purine biosynthetic pathway in yeast at the ADE1 and ADE2 loci have been studied (Crowley and Kaback, 1984; Meskauskas et al, 1985; Myasnikov et al, 1991). These mutations are used to examine purine metabolism and turnover in yeast and are general nutritional markers for recombinant strains.…”
Section: Introductionmentioning
confidence: 99%
“…These data indicated that the original mutants were respiratory-deficient. The white colony phenotype can be attributed to respiratory deficiency because the development of a pink color in the ade2 genetic background found in the eki1⌬ (KS101) and cki1⌬ eki1⌬ (KS106) mutants and the parent W303-1B strain would be dependent on oxidative phosphorylation (73). Another characteristic common to respiratory-deficient mutants is the inability to grow at elevated temperatures (74).…”
Section: Resultsmentioning
confidence: 99%
“…This mutation leads to the accumulation of red pigment, the product of polymerization of aminoimidazole ribotide (AIR) (Smirnov et al , 1967). The red pigment can be involved in interesting physiological effects, such as modification of DNA cleavage (Meskauskas et al , 1985).…”
Section: Introductionmentioning
confidence: 99%